Recent review of BixMOy (M=V, Mo, W) for photocatalytic CO2 reduction into solar fuels. (November 2022) - Ren, Guangmin; Wei, Zixuan; Liu, Sitong; Shi, Meng; Li, Zizhen; Meng, Xiangchao
Abstract: The utilization of solar energy for CO2 conversion not only enables a green and low-carbon recycling of CO2 with renewable energy, but also solves ecological problems. Bix MOy (M = V, Mo, W) materials have typical layered structures and unique electronic properties that provide suitable band gaps and potential to meet the basic conditions for CO2 reduction. However, pristine Bix MOy faces with problems such as small specific surface area, insufficient active sites, low charge carriers' separation and utilization efficiency. This review comprehensively described the basic principles and reaction pathways of photocatalytic CO2 reduction, and further presented the research progress of Bix MOy catalysts in CO2 conversion reactions. In this perspective, we further focus on the design concepts and modification strategies to improve the photocatalytic CO2 reduction activity of Bix MOy, such as morphology control, constructing surface vacancies and heterojunction fabrication. Finally, based on representative researches, the present review will be expected to provide updated information and insights for developing advanced Bix MOy materials to further improve CO2 reduction activity and selectivity. Graphical abstract: Materials engineering toward enhancing photocatalytic CO2 conversion of Bix MOy (M = V, Mo, W). Image 1 Highlights: The review aims to explore the potential of the Bix MOy materials for photocatalytic CO2 reduction. Modification strategies including morphology control, fabrication of defects and heterojunctions, carbonaceous materials coupling, etc. The challenges and future prospects in the Bix MOy photocatalytic CO2 conversion field are proposed.